Kyrgyz Republic Economic Update No. 6, Fall/Winter 2017 : A Robust Recovery with Underlying Weaknesses - Dubashov, Bakyt (World Bank, Washington, DC, 2018)
The Kyrgyz economy appears to have recovered from the 2014-2015 external shocks. Over the first nine months of 2017, real Gross Domestic Product (GDP) expanded by five percent, year-on-year, thanks to improvements in the external environment and a continued expansionary fiscal policy, which were mirrored by a strong gold production and a strengthening in domestic demand. The Kyrgyz economy performed robustly over 2017. Macroeconomic policies were supportive to growth, but the fiscal stance has deteriorated significantly and inflation has tilted upwards. Growth is estimated to have decelerated toward the end of 2017, and expected to pick up in 2018. The economy is expected to remain dependent on remittances. Private inflows will continue to support household incomes and boost domestic demand, but they also come with challenges. The first part of this Economic update analyzes recent macroeconomic trends and presents an assessment of the country’s short- and medium-term outlook. The Special Focus section discusses recent trends in labor migration and the implications of remittance dependence for macroeconomic policies.